1H and 13C NMR study of perdeuterated pyrazoles. Issue 4 (1997) - Jimeno Jimeno, María Luisa María Luisa; Jagerovic Jagerovic, Nadine Nadine; Elguero Elguero, José José; Junk Junk, Thomas Thomas; Catallo Catallo, W. James W. James
Abstract : The 1 H and 13 C chemical shifts as well as the 1 H– 2 H and 2 H– 13 C coupling constants of perdeuterated 3, 5-dimethylpyrazole and 3, 5-diphenylpyrazole have been measured and the values compared with those of the unlabelled compounds.